2019
DOI: 10.1016/j.scitotenv.2018.10.223
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of full-scale tertiary wastewater treatment by UV-C based-AOPs: Removal or persistence of antibiotics and antibiotic resistance genes?

Abstract: This research reports for the first time the full-scale application of different homogeneous Advanced Oxidation Processes (AOPs) (H 2 O 2 /UV-C, PMS/UV-C and PMS/Fe(II)/UV-C) for the removal of antibiotics (ABs) and antibiotic resistance genes (ARGs) from wastewater effluent at Estiviel wastewater treatment plant (WWTP) (Toledo, Spain). AOPs based on the photolytic decomposition of H 2 O 2 and peroxymonosulfate tested at low dosages (0.05-0.5 mM) and with very low UV-C contact time (4-18 s) demonstrated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Very recently, Rodríguez-Chueca et al [217] have reported that AOPs, in general, improved the efficiency of UV-C on the removal of antibiotics. When applying the harshest operating conditions (0.5 mM dosage of oxidants and 7s of UV-C contact time), three antibiotics (ciprofloxacin, metronidazole, and sulfamethoxazole) were similarly removed using peroxymonosulfate and H 2 O 2 as oxidants, four antibiotics (azithromycin, clindamycin, ofloxacin, and trimethoprim) were removed more efficiently using peroxymonosulfate, and three (clarithromycin, sulfadiazine, and sulfapyridine) using H 2 O 2 .…”
Section: Prospects and Challenges Of Aopsmentioning
confidence: 99%
“…Very recently, Rodríguez-Chueca et al [217] have reported that AOPs, in general, improved the efficiency of UV-C on the removal of antibiotics. When applying the harshest operating conditions (0.5 mM dosage of oxidants and 7s of UV-C contact time), three antibiotics (ciprofloxacin, metronidazole, and sulfamethoxazole) were similarly removed using peroxymonosulfate and H 2 O 2 as oxidants, four antibiotics (azithromycin, clindamycin, ofloxacin, and trimethoprim) were removed more efficiently using peroxymonosulfate, and three (clarithromycin, sulfadiazine, and sulfapyridine) using H 2 O 2 .…”
Section: Prospects and Challenges Of Aopsmentioning
confidence: 99%
“…This effect was attributed to the UV photons scavenger by oxidants in detriment to DNA photoabsorption, reducing the direct damage to the genes. In addition, the LOQ of the investigated genes was not reached probably due to the very low contact time (4 s of UV-C irradiance) [ 33 ], which were much lower than those covered in the present study (60 min of treatment time, corresponding to 300 s of UV-C irradiance).…”
Section: Resultsmentioning
confidence: 77%
“…UV-C driven SR-AOPs have been studied for the degradation of different contaminants and for the inactivation of several pathogens, but only few studies involve the use of complex matrices [ 14 , 15 , 31 , 32 , 33 ]. Mahdi-Ahmed et al (2014) reported Ciprofloxacin (CIP) oxidation by UV-based AOPs, comparing the performances of three oxidants, PMS, PS, and H 2 O 2 in DW and UWW.…”
Section: Resultsmentioning
confidence: 99%
“…Rodriguez‐Chueca et al (2019) applied homogeneous AOPs (H 2 O 2 /UV‐C, PMS/UV‐C, and PMS/Fe(II)/UV‐C) in full‐scale to treat antibiotics and ARGs. To remove antibiotics, 0.5 mmol PMS with 7‐s UV‐C had the greatest removal rate.…”
Section: Chemical Processesmentioning
confidence: 99%